Anatomical plating versus titanium elastic nailing for displaced midshaft clavicle fractures: a prospective comparative study - Philip, Ashish; Suranigi, Shishir Murugharaj; ., Lingaraj; Rengasamy, Kanagasabai; Najimudeen, Syed (International Journal of Research in Orthopaedics, 2021)
Background: Plate fixation has become the standard operative method for fixing displaced midshaft clavicle fractures. Over the years, TENS has also gained lot of attention due to its minimal invasive nature, smaller scar and reduced operative time. The purpose of this study was to compare the functional outcome of middle third displaced clavicle fractures treated either by plate or intra medullary TENS fixation using Constant Murley score and disability of the arm, shoulder and hand score. Methods: A prospective randomised study was conducted from January 2010 to September 2016 at our institute on patients with displaced midshaft clavicle fractures. A total of 56 patients (TENS; n=25, plating; n=31), classified according to orthopaedic trauma association classification underwent midshaft clavicle fixation. They were followed-up for a minimum period of 1 year. Results: Length of the scar in the TENS group was significantly smaller when compared to the incision in the plating group (1.86±1.23 and 11.01±3.29 cms respectively, p<0.001). The Constant shoulder score measured at the end of 1 year was 90.77±9.01 for the TENS group and 92.63±6.04 for the plating group, not significant statistically (p=0.269). The mean DASH score was also not significantly different (p=0.552) between the TENS group and the plating group, at 6.01±11.09 and 6.32±10.33 respectively. Conclusions: In comparison with plate fixation, the nailing procedure is less invasive, requires smaller incisions and has a shorter duration of hospital stay with no statistically significant difference in terms of functional outcome. Hence, TENS technique is recommended for the fixation of displaced mid-shaft non-/minimal comminuted clavicular fractures, especially for young individuals and can be used as an alternative to plate fixation.